2016
DOI: 10.1634/theoncologist.2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to a Head and Neck Cancer-Specific Frailty Index and Its Clinical Implications in Elderly Patients: A Prospective Observational Study Focusing on Respiratory and Swallowing Functions

Abstract: Introduction. Frailty refers to a decreased physiologic reserve in geriatric patients and its importance in terms of treatment planning and outcome prediction has been emphasized in oncologic practices for older patients with cancer. We investigated the clinical implications of a head and neck cancer (HNC)-specific frailty index suggested by prospective clinical and functional evaluations of HNC patients. Materials and Methods. We analyzed data on 165 elderly patients with HNC who were prospectively enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
0
32
0
2
Order By: Relevance
“…A further 7 of 95 studies had at least one aspect of methodological quality rated as good; hypothesis testing was the measurement property with the highest number of good ratings (4 of 7). Overall, 70 of 95 studies had at least one aspect of methodological quality rated as fair 3,9,26,27,40,42,43,45,46,49–58,60,62,64,67–70,72–75,79–85,87–97,99–101,104,105,107–116,118,122,123,125–127 . Hypothesis testing had the greatest number of fair ratings (65 of 70).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 7 of 95 studies had at least one aspect of methodological quality rated as good; hypothesis testing was the measurement property with the highest number of good ratings (4 of 7). Overall, 70 of 95 studies had at least one aspect of methodological quality rated as fair 3,9,26,27,40,42,43,45,46,49–58,60,62,64,67–70,72–75,79–85,87–97,99–101,104,105,107–116,118,122,123,125–127 . Hypothesis testing had the greatest number of fair ratings (65 of 70).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of 48 tools include items from existing psychiatric assessment tools, five of which use items from the Centre for Epidemiological Studies‐Depression Scale (CES‐D) . Other tools included the Hospital Anxiety and Depression Scale (HADS) and the Beck Depression Inventory II . However, in most of these cases, items included from existing mental health tools were used to assess fatigue (6 of 12), rather than the presence of mental illness (5 of 12) …”
Section: Resultsmentioning
confidence: 99%
“…Thus, dysphagia must be identified at an early stage and patients provided with nasogastric tube feeding to avoid pulmonary complications. This was underscored in a recent article that demonstrated that pretreatment swallowing and respiratory dysfunctions in elderly patients with head and neck cancer significantly impact early post‐treatment morbidity and mortality, and that frailty assessment comprising these functions has a greater prognostic significance than conventional screening methods to assess fitness for surgery . However, dysphagia and aspiration has not been reported to be a problem in the reviewed articles.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson Dysphagia Index (MDADI) that were more predictive of 2-year morbidity and mortality than a “traditional” GA at baseline. 32 …”
Section: Methodsmentioning
confidence: 99%